Patient safety in a general hospital's psychiatric hospitalization unit: a phenomenological study - Andressa de Oliveira; Vanessa Pellegrino Toledo
ABSTRACT Objective: To understand the meaning of patient safety for a multiprofessional team in a psychiatric unit of a general hospital. Method: Qualitative study adopting the social phenomenological framework, employing open-ended interviews whose content was analyzed and discussed based on the literature through the elaboration of categories of analysis. Results: Eleven open-ended interviews were conducted. The meaning of psychiatric patient safety was understood to encompass team management experiences that emphasize physical coercion and control of symptomatology while indicating the expectation of elaborating new procedures that account for humanization. It also includes issues regarding organizational composition and experienced difficulties concerning physical structure, its interference in the process of providing safe care and expectations of improvement. Conclusion: This study analyzed the conception of patient safety in the multiprofessional team viewpoint, considering socio-historical and cultural contexts and the mutual relations that are part of meaning construction in the study setting.